ANALISA PERESEPAN DAN INTERAKSI KOMBINASI DUA MACAM ANTIBIOTIK INTRAVENA DI RUMAH SAKIT X TANGERANG SELATAN - Chusun, Chusun; Retno, Fitriani; Yosep, Fauzi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
One of the mainstay drugs to treat infections is antimicrobials, including antibacterials/antibiotics, antifungals, antivirals and antiprotozoa. Antibiotics are drugs used in infections caused by bacteria. Antibiotics that are not used wisely can lead to resistance problems. Therefore, the use of antibiotics must follow a rational strategy of prescribing antibiotics. Irrational prescribing will increase the occurrence of drug side effects, drug interactions, medical costs and result in decreased patient compliance in taking drugs. The purpose of this study was to determine the pattern of prescribing combinations of intravenous antibiotics in one prescription sheet and their interactions. This research is a type of quantitative research, with descriptive methods and using retrospective data. The population in this study were all prescription sheets of inpatients who had been served at the X Hospital Pharmacy Installation for the period January 1 to March 31, 2021. The samples were all prescription sheets containing a combination of 2 (two) intravenous antibiotics (injection or infusion), all of which totaling 170 sheets. The results showed that there were more male patients than female patients, namely 52.3% with the largest age range between 46-55 years (29.41%). Of the 15 combinations of 2 (two) intravenous antibiotics, there were 6 combinations that had moderate pharmacodynamic interactions. Moderate interactions are clinically significant, usually avoided in combination or used only in special circumstances and with close monitoring of health workers. Of the 170 prescription sheets, 135 sheets (79.4%) were prescribed by internal medicine specialists. All intravenous antibiotics prescribed according to the X Hospital Formulary and the National Formulary.